Unveiling the Potential: Biodegradation of Plastics by Algae : A Review - Agate, Suyash; Shivalkar, Shreya; Khan, Almeera; Soni, Shouriehebal (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Plastic pollution is a serious environmental and ecological issue and disposal methods such as burying, burning, and chemical breakdowns harm biodiversity. To reduce those negative impacts it is crucial to find effective plastic-degrading techniques. According to recent research studies, biodegradation of plastic by microalgae is likely a sustainable solution.This paper reviews the research done on the role of algae in plastic biodegradation, current research revealed that numerous algae and cyanobacterial species such as Chlamydomonas reinhardtii, Scenedesmus dimorphus, Oscillatoria and Chlorella vulgaris, degrade various types of plastic by using enzymes such as ligninolytic and exopolysaccharide. These species are useful in reducing “white pollution”. This study gives a brief process of algal biodegradation of plastic by various species giving insights into the previous 07 years of research work and the future potential in this field.